(untitled) (International Journal of Engineering and Computer Science, 2015)
Opinion mining and sentiment analysis is the significant key field of Natural Language Processing. Number of users shared their thoughts and opinions on micro blog services. Social networks serve as the source of valuable platform for tracking and analyzing public sentiment of different people about different domains/products. Twitter is one of the most popular social sites where the millions of users share their opinions. Public sentiment analysis is a process to identify positive and negative opinions, emotions and evaluations in text. This paper reviewed and analysed number of techniques for public sentiments analysis and its classification.